TER Sport Complex Reservation System / Muhamad Hatta Mohd Khalid - Mohd Khalid, Muhamad Hatta (2018)
Nowadays, managing the reservation process using a traditional approach like using pen and paper are not only time consuming, but also sometimes inefficient resulting in the false recording of information. The problem with this approach when the management is difficult in report generating for the customer reservation and it requires lots of paper are part of our non-renewable natural resources. The aim of this paper is to develop an accurate, fast and very efficient reservation system to computerize the traditional way of recording reservation, which is implemented on computer system. It can run on multiple browsers likes Google, Mozilla and others. For TER Sport Complex Reservation System, it can be used by manager, staff and all customers for recording and managing the reservation process. This system stores data into MySqli database The management also can approved the reservation made from customers and communicate with customers through this system.